Integrin Activation: Implications for Axon Regeneration - Cheah, Menghon (Cells, 2018)
Integrin activation is essential for creating functional transmembrane receptors capable of inducing downstream cellular effects such as cell migration, cell spreading, neurite outgrowth and axon regeneration. Integrins are bidirectional signalling molecules that mediate their effects by ‘inside–out’ and ‘outside–in’ signalling. This review will provide a detailed overview of integrin activation focusing on intracellular activation in neurons and discussing direct implications in the regulation of neurite outgrowth and axon regeneration.